UKM Students Global Mobility Programme to Niigata: Gaining New Experience, Medical Knowledge and Culture in Japan - Shahruz Idzwan, Azmi; Syed Sharizman, Syed Abdul Rahim; Zahir Izuan, Azhar (Universiti Kebangsaan Malaysia, 2015)
In the middle of January 2014 during the winter season, three post graduate students from Community Health Department, Faculty of Medicine, Universiti Kebangsaan Malaysia (UKM) were invited to have a taste of experience on public health practice in Niigata Graduate School of Medicine & Dental Sciences (NU) under Division of International Health (Public Health). This is the fourth group which was invited through the student exchange program between both universities. The journey took almost 7 hours from Kuala Lumpur International Airport to Narita International Airport by plane; and another 2 hours by bullet train (shinkansen) ride from Tokyo City to Niigata prefecture. The cold weather, which was below 2 degree Celsius, did not stop our burning desire to step into the country which was well known for its modernization and yet still upholding its ancient and renowned tradition.